Functionalized silica aerogels for gas-phase purification, sensing, and catalysis: A review - Amonette, James E.; Matyáš, Josef (Microporous and mesoporous materials, 2017)
Silica aerogels have a rich history and offer an unusual assembly of gas- and solid-phase properties that has lent them to many diverse applications. This review starts with a brief discussion of the fundamental issues driving the movement of gases in silica aerogels and then proceeds to provide an overview of the work that has been done with respect to the purification of gases, sensing of individual gases, and uses of silica aerogels as catalysts for gas-phase reactions. Salient features of the research behind these different applications are presented, and, where appropriate, critical aspects that affect the practical use of the aerogels are noted. Specific sections under the gas-purification category focus on the removal of airborne nanoparticles, carbon dioxide, volatile organic compounds, sulfur gases and radioactive iodine from gas streams. The use of silica aerogels as sensors for humidity, oxygen, hydrocarbons, volatile acids and bases, various non-ammoniacal nitrogen gases, and viral particles is discussed. With respect to catalysis, the demonstrated use of silica aerogels as supports for oxidation, Fischer-Tropsch, alkane isomerization, and hydrogenation reactions is reviewed, along with a section on untested catalytic formulations involving silica aerogels. A short section focuses on recent developments in thermomolecular Knudsen compressor pumps using silica aerogel membranes. The review continues with an overview of the production methods, locations of manufacturing facilities globally, and a brief discussion of the economics before concluding with a few remarks about the present and future trends revealed by the work presented. [Display omitted] •Functionalized silica aerogels have unique gas-phase chemistry for many applications.•Can purify gases by removing particles, CO2, VOCs, sulfur gases, and iodine.•Can sense humidity, oxygen, hydrocarbons, acids, bases, nitrogen gases, and viruses.•Can catalyze oxidation, Fischer-Tropsch, isomerization, and hydrogenation reactions.•Are manufactured globally in response to increasingly favorable economic trends.